2022
DOI: 10.1111/cns.13834
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the effects of caffeine in a neonatal rat model of hypoxic‐ischemic white matter damage

Abstract: Aim White matter damage (WMD) is the main cause of cerebral palsy and cognitive impairment in premature infants. Although caffeine has been shown to possess neuroprotective effects in neonatal rats with hypoxic‐ischemic WMD, the mechanisms underlying these protective effects are unclear. Herein, proteins modulated by caffeine in neonatal rats with hypoxic‐ischemic WMD were evaluated. Methods We identified differential proteins and performed functional enrichment analyses between the Sham, hypoxic‐ischemic WMD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 67 publications
(128 reference statements)
1
13
0
Order By: Relevance
“…In our study, early Ibu in RA as well as Caff in hyperoxia seemed to favor myelination, while late treatment caused reduced myelination (data not shown). The protective effect of Caff on HIE‐induced WM damage was shown in neonatal rats (Yang et al, 2022), consistent with our findings. Overall, IH seems to negatively affect the process of myelination regardless of early or late treatment.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, early Ibu in RA as well as Caff in hyperoxia seemed to favor myelination, while late treatment caused reduced myelination (data not shown). The protective effect of Caff on HIE‐induced WM damage was shown in neonatal rats (Yang et al, 2022), consistent with our findings. Overall, IH seems to negatively affect the process of myelination regardless of early or late treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, this non-linear relationship between caffeine concentration and its impact on protein hydrolysis may be indicative of the complex pharmacokinetic interactions of caffeine with enzymes, affecting their activity and leading to pharmacokinetic interactions with medications and other compounds (Romero-Martínez et al, 2021; Rasmussen et al, 1998). Additionally, the inhibitory effect of caffeine on speci c enzymes has been explored in different biological systems, highlighting its potential as an enzyme inhibitor in various contexts (Liu et al, 2022;Selby & Sancar, 1990). Furthermore, the non-linear relationship between caffeine concentration and protein hydrolysis may be in uenced by the diverse physiological effects of caffeine.…”
Section: Discussionmentioning
confidence: 99%
“…They specifically target RIG-I or TAB2 for K63-linked polyubiquitination, promoting RIG-I or TAB2-mediated NF-κB activation. More notably, prior research revealed that TRIM67 was markedly decreased after ischemic stroke [ 27 ] and could inhibit NF-κB activation and lessen the release of inflammatory components, hence having a certain anti-inflammatory impact [ 26 ]. The probable mechanism of TRIM67 was investigated by specifically targeting IκBα, a crucial negative regulator of NF-κB signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study claimed that TRIM67 inhibits TNFα-triggered activation by competitively binding β-TrCP to IκBα [ 26 ]. Meanwhile, proteomic analysis found that TRIM67 expression dramatically decreases following stroke [ 27 ], implying that it might be involved in ischemic stroke. However, the significance and underlying mechanisms of NF-κB regulation of TRIM67 are not fully understood in ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%